The theory and methodology of scientific research on the implementation of human-centered management in organizations’ HR management strategies - Zachosova Nataliia; Зачосова Н.; Zacsoszová N. (II. Rákóczi Ferenc Kárpátaljai Magyar Főiskola, 2025)
Abstract. The aggressively capitalist model of economic development, wherein the primary objective of economic entities was profit generation at any cost, has proven ineffective over the long term, as evidenced by environmental indicators and, in some cases, global social metrics. The preservation of human capital in an environment characterized by uncertainty and risks, which are abundant in today’s world, must become the central priority of global development. A potential tool for maintaining and advancing the quality of personnel available to modern enterprises is human-centered management. The aim of this study is to provide a theoretical and methodological substantiation of proposals for incorporating human-centered management into the HR management strategies of organizations. The study explores the concept of human-centrism as a contemporary humanistic paradigm that shapes approaches to personnel management amid economic, social, and cultural transformations. A three-stage model for integrating human-centrism into management processes is proposed, ranging from meeting employees’ basic needs to their full-fledged involvement in strategic planning. The research examines the economic expectations of young people after the conclusion of the war in Ukraine and their strategic visions for their economic future (specifically in the context of employment). The article highlights the importance of state-level and private-sector support for processes aimed at developing a qualified talent pool, establishing coherent communication mechanisms, stimulating innovation, and creating favourable conditions for harmonizing employees’ work and personal lives. The findings demonstrate that a human-centered approach to HR management can foster workforces characterized by high levels of motivation, loyalty, and professional efficiency, which are critical components in shaping a positive organizational image in the labour market.

A gazdasági fejlődés agresszívan kapitalista modellje, amelyben a gazdasági egységek elsődleges célja a profittermelés volt mindenáron, hosszú távon hatástalannak bizonyult, amint azt a környezeti mutatók és egyes esetekben a globális társadalmi mutatók is bizonyítják. A globális fejlődés központi prioritásává kell válnia a humán tőke megőrzésének egy olyan környezetben, amelyet a mai világban bőségesen jelenlévő bizonytalanság és kockázatok jellemeznek. A modern vállalatok rendelkezésére álló munkaerő minőségének fenntartására és fejlesztésére szolgáló lehetséges eszköz az emberközpontú menedzsment. A tanulmány célja, hogy elméleti és módszertani alátámasztást nyújtson az emberközpontú menedzsmentnek a szervezetek HR-menedzsment stratégiáiba való beépítésére vonatkozó javaslatok elméleti és módszertani megalapozására. A tanulmány az emberközpontúság fogalmát vizsgálja, mint olyan kortárs humanista paradigmát, amely a gazdasági, társadalmi és kulturális átalakulások közepette alakítja a személyzeti menedzsment megközelítését. Háromlépcsős modellt javasol az emberközpontúságnak a vezetési folyamatokba való integrálására, amely az alkalmazottak alapvető szükségleteinek kielégítésétől a stratégiai tervezésbe való teljes körű bevonásukig terjed. A kutatás a fiatalok gazdasági elvárásait vizsgálja az ukrajnai háború befejezése után, valamint a fiatalok gazdasági jövőjükkel kapcsolatos stratégiai elképzeléseit (különösen a foglalkoztatással összefüggésben). A cikk kiemeli az állami és magánszektorbeli támogatás fontosságát a képzett tehetségállomány fejlesztését, a koherens kommunikációs mechanizmusok kialakítását, az innováció ösztönzését és a munkavállalók munka- és magánéletének összehangolását elősegítő kedvező feltételek megteremtését célzó folyamatok számára. Az eredmények azt mutatják, hogy az emberközpontú megközelítés a HR-menedzsmentben elősegítheti a magas szintű motivációval, lojalitással és szakmai hatékonysággal jellemezhető munkaerőt, amely kritikus összetevője a pozitív szervezeti imázs kialakításának a munkaerőpiacon.

Резюме. Агресивно капіталістична модель економічного розвитку, за якої основною метою функціонування суб’єктів господарювання було отримання прибутку за будь-яку ціну, виявилась неефективною на довгостроковому часовому горизонті, про що свідчать екологічні індикатори, а подекуди і соціальні глобальні показники. Збереження людського капіталу в умовах невизначеності та ризиків, якими перенасичений сучасний світ, має стати основним пріоритетом сталого глобального розвитку. Інструментом збереження та розвитку до необхідного сучасному підприємництву якісного рівня наявного у компаній персоналу може стати людиноцентроване управління. Метою дослідження є теоретико-методичне обґрунтування пропозицій щодо можливостей запровадження людиноцентрованого управління в стратегії HR-менеджменту організацій. У статті досліджено концепцію людиноцентризму як сучасної гуманістичної парадигми, що визначає підходи до управління персоналом в умовах економічних, соціальних та культурних трансформацій. Запропоновано трьохетапну модель інтеграції людиноцентризму в управлінські процеси: від базового задоволення потреб працівників до їх повноцінного залучення у стратегічне планування діяльності організацій. Проаналізовано економічні очікування молодих людей після завершення війни в Україні та стратегічні візії молоді власного економічного майбутнього (у контексті працевлаштування). У статті звернено увагу на важливість підтримання на державному рівні та у приватному секторі процесів формування кваліфікованого кадрового резерву, злагоджених комунікаційних механізмів, стимулювання інноваційної діяльності та створення сприятливих умов для гармонізації роботи й особистого життя працівників. Результати дослідження демонструють, що людиноцентрований підхід в HRменеджменті здатний формувати робочі колективи з високим рівнем мотивації, лояльності та професійної ефективності, що є важливим елементом створення позитивного іміджу організацій на ринку праці.
Теорія та методологія наукових досліджень можливостей запровадження людиноцентрованого управління в стратегії HR-менеджменту організацій
A tudományos kutatás elmélete és módszertana az emberközpontú menedzsment bevezetésének lehetőségeiről a szervezetek HR menedzsment stratégiájába
Редакційна колегія: https://aab-economics.kmf.uz.ua/aabe/about/editorialTeam
Зміст: https://aab-economics.kmf.uz.ua/aabe/issue/view/8
Keywords: human-centered; human-centered management; scientific research methodology; HR management; personnel management; strategy; strategic management